INTEGRASI PENDIDIKAN MULTIKULTURAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) UNTUK MEMBENTUK KARAKTER TOLERAN - Siti Nurhasanah (STAI Pelabuhan Ratu, 2021)
This study aims to describe or explain the integration of multicultural education in learning Islamic religious education (PAI) to form a tolerant character at SDN 037 Sabang Bandung. This research method uses a qualitative type with a descriptive approach. Data collection methods used are observation, interviews and documentation. The conclusions of this study are: 1) The form of integration of multicultural education in learning Islamic religious education at SDN 037 Sabang Bandung there are six forms of integrated multicultural values ​​in learning Islamic religious education at SDN 037 Sabang Bandung, the six forms of values ​​are inclusive values, humanist values, values ​​of tolerance, values ​​of mutual assistance, democracy and ukhuwah. 2) The implementation of the integration of multicultural education in learning Islamic religious education at SDN 037 Sabang Bandung is carried out in learning planning, learning implementation, learning evaluation. 3) The impact of multicultural education in Islamic religious learning (PAI) in forming a tolerant character at SDN 037 Sabang Bandung, including: a) Creating a comfortable and conducive learning atmosphere; b) School activities run smoothly and have a high tolerance; c) The realization of religious harmony and harmony in diversity; d) Avoiding conflicts and divisions; e) The creation of a culture of mutual respect, respect and acceptance of differences.